Tea leaves moisture measurement and prediction using RF waveguide antenna - Shyh Yau, Tein; Yi Lung, Then; Hieng Tiong, Su (2018)
This paper proposed a microwave reflection method by using a horn antenna at 10.3GHz to determine m.c. of tea leaves from 0% to 10.5%. The tea leaves are filled inside an acrylic container whereas a horn antenna is placed on the open ended of the container. Reflection coefficient, S 11 is collected and its relationship between gravimetric (m.c g ) and volumetric moisture content (m.c v ) are fitted in two polynomial equations respectively. The equations are used to predict m.c. of tea leaves. The maximum error for the predicted m.c g is 0.52% whereas the maximum error of predicted m.c v is 0.233%.